Strategic advantages of good supplier relations in the Indian automobile industry - Khare, Anshuman (Technovation)
The author examines industry/supplier relationships in the automobile industry, demonstrating the strategic advantages of Indo/Japanese collaboration. He also analyses similarities and differences between situations in the two countries.